Identification of the physical characteristics that discriminate between competitive levels and specialties of alpine skiers - Impellizzeri, F. M.; Rampinini, E.; Freschi, M.; Maffiuletti, N. A.; Bizzini, M.; Mognoni, P. (Science and Skiing IV, 2009)
INTRODUCTION: Studies examining the physical determinants of alpine skiing performance have reported contradictory or inconsistent results. The aim of the present study was to identify the physical characteristics that can discriminate the competitive level and the specialty of alpine skiers using a multivariate approach.